Decarbonization pathways in developing Asia: Evidence from modeling scenarios - Manisha Pradhananga; David A. Raitzer; Iva Sebastian-Samaniego; Daryll Naval (Asian Development Bank (ADB), 2023)
Unless developing Asia decarbonizes its development, global warming is unlikely to stay below the internationally agreed limit of 2êC above preindustrial levels. Integrated assessment modeling offers insights into how a low carbon transition can be achieved. The Sixth Assessment Report of the Intergovernmental Panel on Climate Change incorporated an ambitious model intercomparison effort that compiled thousands of model-scenario combinations to consider low carbon development pathways. This paper explores the evidence within that database to consider decarbonization pathways for developing Asia. Overall, a comparison of the major models finds strong consistency in the transformation of the energy sector required to achieve Paris Agreement goals. This includes a rapid decline in the share of coal-a mainstay of the power sector in developing Asia-and a substantial rise in renewable energy. The cost of the transition can be relatively low if mitigation efforts are efficient, as assumed in the models.
Keywords: C61; D58; Q4; Q54; 330; climate change; integrated assessment model; mitigation; energy; Paris Agreement; NDCs